2022
DOI: 10.1111/cogs.13109
|View full text |Cite
|
Sign up to set email alerts
|

Morningness‐Eveningness Preference, Time Perspective, and Passage of Time Judgments

Abstract: Recent studies have shown that making accurate passage of time judgments (POTJs) for long‐time intervals is an important cognitive ability. Different temporal domains, such as circadian typology (biological time) and time perspective (psychological time), could have an effect on subjective POTJs, but few studies have investigated the reciprocal influences among these temporal domains. The present study is the first systematic attempt to fill this gap. A sample of 222 participants (53.20% females; 19–60 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 84 publications
(155 reference statements)
2
11
0
Order By: Relevance
“…The total score ranges from 4 to 25 and higher scores indicate a shift toward morningness. Although Beracci et al [ 41 ] reported a Cronbach’s alpha of below 0.70, this value was in line with the α level reported in the Italian population [ 47 ]. More importantly, the concurrent and construct validity of the rMEQ has been demonstrated in an Italian context [ 45 ].…”
Section: Methodssupporting
confidence: 83%
See 4 more Smart Citations
“…The total score ranges from 4 to 25 and higher scores indicate a shift toward morningness. Although Beracci et al [ 41 ] reported a Cronbach’s alpha of below 0.70, this value was in line with the α level reported in the Italian population [ 47 ]. More importantly, the concurrent and construct validity of the rMEQ has been demonstrated in an Italian context [ 45 ].…”
Section: Methodssupporting
confidence: 83%
“…To evaluate the TP, we administered the Italian version of the ZTPI [ 22 ], adopted by Beracci et al [ 41 ]. This version of the ZTPI contained 56 items rated on a 5-point Likert scale (1 = very uncharacteristic of me; 5 = very characteristic of me).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations